Inactivation of mTORC1 Signaling in Osterix‐Expressing Cells Impairs B‐cell Differentiation. (29th January 2018) - Wang, Yongkui; Xiao, Min; Tao, Chen; Chen, Jing; Wang, Zhenyu; Yang, Jun; Chen, Zhenguo; Zou, Zhipeng; Liu, Anling; Cai, Daozhang; Jiang, Yu; Ding, Changhai; et al.
ABSTRACT: Osteoblasts provide a microenvironmental niche for B‐cell commitment and maturation in the bone marrow (BM). Any abnormity of osteoblasts function may result in the defect of B lymphopoiesis. Signaling from mechanistic target of rapamycin complex 1 (mTORC1) has been implicated in regulating the expansion and differentiation of osteoblasts. Thus, we raise a hypothesis that mTORC1 signaling in osteoblasts plays a vital role in B‐cell development. Inactivation of mTORC1 in osterix‐expressing cells (mainly osteoblast lineage) through Osx‐Cre‐directed deletion of Raptor (an mTORC1‐specific component) resulted in a reduction in the total B‐cell population in the BM, which was due to a block in early B‐cell development from the pro‐B to pre‐B cell stage. Further mechanistic studies revealed that this defect was the result of reduction of interleukin‐7 (IL‐7) expression in osterix‐expressing immature osteoblasts, which caused the abnormality of IL‐7/Stat5 signaling in early B lymphocytes, leading to an increased apoptosis of pre‐B plus immature B cells. In vitro and in vivo studies demonstrated that the addition of exogenous IL‐7 partially restored B lymphopoiesis in the BM of Raptor mutant mice. Furthermore, total BM cells cultured in conditioned media from Raptor null immature osteoblasts or media with anti‐IL‐7 neutralizing antibody failed to differentiate into pre‐B and immature B cells, indicating that inactivation of mTORC1 in immature osteoblast cannot fully support normal B‐cell development. Taken together, these findings demonstrate a novel role for mTORC1 in the regulation of bone marrow environments that support B‐cell differentiation via regulating IL‐7 expression. © 2017 American Society for Bone and Mineral Research.